Investigating Pre-service Science, Technology, and Mathematics Teachers’ Attitudes toward Climate Change in Nigeria - Oladipo, Adenike; Awofala, Adeneye O. A.; Osokoya, Modupe M. (Journal of Educational Sciences, 2020)
The study investigated attitudes toward climate change among 480 pre-service science, technology, and mathematics (STM) teachers from four higher institutions of learning in Southwest, Nigeria using the quantitative research method within the blueprint of the descriptive survey design. Data collected using climate change attitude survey were analysed using the descriptive statistics of percentages, mean, and standard deviation and inferential statistics of factor analysis and independent samples t-test. Findings revealed that attitudes toward climate change assessed by the climate change attitude survey was a multi-dimensional construct (perceived beliefs component and intentions component). Gender differences in attitudes toward climate change among pre-service STM teachers were not significant even at the subscale level of perceived beliefs and intentions. In addition, the pre-service STM teachers showed a moderate level of attitudes toward climate change. In conclusion, there is need for a concerted effort to protect the earth from increased weather variability and the Nigerian government at all levels has both international and domestic commitments to reduce greenhouse gas emissions to ensuring sustainable human development. Future studies in Nigeria and elsewhere should conduct a confirmatory factor analysis on the climate change attitude survey to further generalise the findings of this study.